A review on thermo-mechanical properties of bi-crystalline and polycrystalline 2D nanomaterials. Issue 2 (3rd March 2020) - Sharma, Bharat Bhushan; Parashar, Avinash
Abstract: Due to outstanding properties, graphene and h-BN nanosheets are emerging as a potential candidate for wide spectrum of applications in the field of engineering and bio-medical science. Graphene and h-BN nanosheets have comparable mechanical and thermal properties, whereas due to high band gap h-BN (∼5eV) have contrasting electrical conductivities. Large size graphene and h-BN nanosheets are synthesized by chemical vapor deposition technique, which results in polycrystalline atomic structure. These polycrystalline nanosheets are characterized either by experimental means or numerical simulations. Experimental techniques are considered as most accurate and practical, but cost and time involved in these techniques limits it application at the nanoscale level. On the other hand, atomistic modeling techniques are emerging as viable alternatives to the experimentations, and are accurate enough to predict the mechanical properties, fracture toughness, and thermal conductivities of polycrystalline graphene and h-BN nanosheets. This comprehensive review article encompasses different characterizing techniques used by the researchers for polycrystalline nanosheets. This review will help in elaborating the properties of polycrystalline graphene and h-BN, and also establishing a perspective on how the microstructure impacts its large-scale physical properties.